A critical exploration of the role of pedagogical documentation in a multimodal grade R classroom: a case study in an urban South African school - Williamson, Morag Margaret (My University, 2016)
The researcher explored the role of pedagogical documentation in a multimodal Grade R classroom. The purpose of the research was to see how pedagogical documentation would work together with a multimodal approach to enhance learning in Grade R children in an urban South African school. A qualitative case study was conducted at a private girls’ school in Johannesburg with a class of 22 Grade R children over the time frame of eight weeks. The children were exposed to a multimodal approach and pedagogical documentation was used in the classroom to make learning visible and to create a focus for discussion and planning. The research focused on an in-depth analysis of five participants although all the children in the class were part of the data collection process. The children demonstrated an ability to make decisions regarding their learning and the curriculum developed around their interests rather than being predetermined by the teacher. The children also developed a willingness to reflect on their learning processes. They took complete ownership of their environment and were able to use all available resources: the environment, the materials, and those emerging from collaboration with their peers and reflecting on their own learning. An open curriculum was successful with children of this age. However, it is proposed that pedagogical documentation together with a multimodal approach would be more effective in collaborative whole school interventions.
Masters of Education by dissertation, University of the Witwatersrand, 2016
Keywords: Early childhood education--South Africa; Multicultural education--South Africa; Curriculum development--South Africa